Catalysts screening for catalytic conversion of glycerol to olefins [electronic resource] - 281229 Nor Fadilah Mohamad (2009)
Project Paper (Sarjana Muda Kejuruteraan (Kimia)) - Universiti Teknologi Malaysia, 2009